Squamous Cell Carcinoma Malignantly Transformed From Frequent Recurrence of a Presacral Epidermoid Cyst: Report of a Case - Wu, Xiaocai; Chen, Chunqiu; Yang, Muqing; Yuan, Xiaoqi; Chen, Hong; Yin, Lu (Frontiers in Oncology, 2020)
BACKGROUD Presacral tumors are rare space occupying lesions that arise in the presacral space. The incidence of presacral tumor has been reported to be 1 in 40 000 to 63 000 patients. An even rarer occurrence is the transformation of a presacral tumor into a squamous cell carcinoma (SCC). CASE SUMMARY A 61-years old man was referred to our hospital for a palpable mass near anus and appeared repeatedly in last ten years. The patient previously underwent two surgeries at another hospital. A posterior approach was implemented in the first two surgeries, and the diagnosis was benign presacral epidermoid cyst. Two months before his admission to our department in 2017, the patient complained of a mass measuring approximately 2-cm around his anus. Physical examination revealed a 2-cm mass at the 12 o’clock direction in chest-knee position. A digital rectal examination indicated a rubbery lesion located in the presacral space. The Pre-operative pelvic magnetic resonance imaging (MRI) confirmed the presence of a 6.8cm*5.2cm*7.3cm mass located at the presacral space. In contrast phase, the center of the lesion exhibited homogenous density without enhancement. The mass was then excised via posterior para-sacral approach with pathological report showing a benign epidermoid cyst after operation. The patient was discharged with full recovery without fecal incontinence. 15 months after being discharged from our hospital, the patient discovered a recurrence at the original site of where the mass previously appeared. Unlike the previous instance, the mass was accompanied with swelling, pain and localized increased skin temperature. Pelvic MRI showed a 3.2cm*7.2cm*5.8cm located at the same place, with no enhance in the core of mass. However, a speckled enhancement was observed on the margin of the lesion. The lesion was completely resected using the same procedure as before with a pathological diagnosis of SCC. The patient underwent chemoradiation therapy and remained disease free for more than one year. Conclusion Although very rare, benign cyst from presacral space can become malignant transformation. This highlights the importance of pre-operative diagnostic tests and evaluation to correctly identify the source of the primary cancer, which is crucial prior to starting adjuvant therapy.